Spherophakia and Ectopia Lentis in a Sturge-Weber Patient: A Case Report - Avalos-Lara, Samuel Josue (Case Rep Ophthalmol, 2020)
Sturge-Weber syndrome (SWS) is a rare, sporadic neurocutaneous disorder, primarily characterized by port-wine stain (PWS) over the ophthalmic division of the trigeminal nerve (V1) territory (hallmark feature) and glaucoma (in 30–60% of cases). Other ocular manifestations include episcleral involvement of the PWS, choroidal vascular malformations, and iris heterochromia. Two previous reports also associated ectopia lentis concomitantly among these cases. However, here we report spherophakia as a novel ophthalmological finding in SWS. A 56-year-old female previously diagnosed with SWS presented to the outpatient clinic complaining of right-sided decreased visual acuity and pain after a fall. Phenotypically, the patient had a PWS around V1 territory and involvement of both eyelids. Previous relevant ocular history included retinal detachment without macular involvement, ocular hypertension, and phacodonesis. The slit-lamp examination showed anterior lens luxation and elevated intraocular pressure (IOP) of 40 mm Hg by tonometry. Prior to the surgical approach, the patient received hypotensive treatment for elevated IOP. After intracapsular lens extraction, measurements were consistent with spherophakia. Postoperatively, the patient underwent optical coherence tomography (OCT). There was cystic macular edema (CME) by OCT and a detached posterior hyaloid membrane. The patient fully recovered with topical treatment of bromfenac for CME. To the best of our knowledge, this is the first report of concomitant anterior lens luxation and spherophakia (novel association) in a SWS patient. Our findings supplement the differential ocular diagnoses in SWS and should be considered in the routine ocular exam, specifically of the anterior segment. CME occurred similar to otherwise healthy eyes. However, in this case, topical anti-inflammatory medications had a good response and were well-tolerated.